The sky painter - Hooi, Cheryl Li Feng (2017)
The Sky Painter is a short animated film about a grandfather learning to treasure his granddaughter. In this society where many people are unrelenting workaholics, it seeks to convey the universal idea that we need to appreciate what we have in life before we lose it, look beyond what is immediately obvious, and that work and duty should never take precedence over family. The film’s various elements such as colour and style have thus been designed to evoke the emotional impact that family has in our lives. This report will detail the process of creating this Final Year Project (FYP) film from its pre-production stages to final rendering, including the challenges faced while conceptualising the project as well as what the group did to overcome technical and skill-based limitations.